Development of Community Creativity and Skills Potential in Supporting the Drug-Prone Area Eradication Program in Tualang Village Serdang Bedagai Regency - Fadli, Ahmad; Amin Hou; Denny Satria; Vivi Asfianti; Syukur Berkat Waruwu (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2025)
The problem of drug use has now become a pandemic that occurs in almost all regions in our country, prone to drugs where drug use is not only consumed by adults but also adolescents and children also become victims. As for the spread, it no longer focuses on big cities but has penetrated the villages, which are massive even with many casualties. This condition of vulnerability must be addressed immediately considering the severe impact that spreads such as social problems and increasing crime. Of course, the program to minimize this impact must be carried out immediately, in line with that, the proposal for community service activities has prepared a program that will provide solutions to these conditions, including: 1. Conducting Anti-Drug Socialization/Counseling training.2, Providing technical training on small business skills in making noodles, 3 Small and Medium Business management training